2007
DOI: 10.1097/mca.0b013e328012a964
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural and medium-term antithrombotic strategies in patients with an indication for long-term anticoagulation undergoing coronary angiography and intervention

Abstract: At our Institution (where standardized protocols are currently not in use), periprocedural and medium-term antithrombotic treatment in patients on long-term anticoagulation undergoing percutaneous coronary intervention with stent implantation showed substantial variability. As a result of the relevant 1-month complication rate, further properly sized and designed studies are warranted to identify the optimal strategies for this patient subset, which is foreseen to progressively increase over the next years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 25 publications
2
45
0
8
Order By: Relevance
“…[1][2][3] Dual antiplatelet therapy (DAPT) with a P2Y 12 inhibitor and aspirin is superior to oral anticoagulation with a vitamin K antagonist in reducing the risk of thrombosis in patients undergoing placement of a first-generation stent, 4 but oral anticoagulation is superior to DAPT in reducing the risk of ischemic stroke in patients with atrial fibrillation. 5 The treatment strategy for patients with atrial fibrillation who have received stents must balance the risk of stent thrombosis and ischemic stroke with the risk of bleeding.…”
mentioning
confidence: 99%
“…[1][2][3] Dual antiplatelet therapy (DAPT) with a P2Y 12 inhibitor and aspirin is superior to oral anticoagulation with a vitamin K antagonist in reducing the risk of thrombosis in patients undergoing placement of a first-generation stent, 4 but oral anticoagulation is superior to DAPT in reducing the risk of ischemic stroke in patients with atrial fibrillation. 5 The treatment strategy for patients with atrial fibrillation who have received stents must balance the risk of stent thrombosis and ischemic stroke with the risk of bleeding.…”
mentioning
confidence: 99%
“…С П Е Ц И А Л И З И Р О В А Н Н Ы Й М Е Д И Ц И Н С К И Й Ж У Р Н А Л 1-2017 АТЕРОТРОМБОЗ мического инсульта и геморрагических ослож-нений [1]. Таким образом, выбор адекватной терапевти-ческой тактики у пациентов с высоким риском ишемических и тромбоэмболических осложне-ний сродни навигации между Сциллой и Хариб-дой.…”
unclassified
“…Таким образом, на сегодняшний день в соста-ве тройной антитромботической терапии реко-мендовано применение только клопидогрела [1,4]. При назначении варфарина в составе трой-ной терапии рекомендовано соблюдение более строгих границ МНО: в нескольких небольших проспективных исследованиях было показано достоверное снижение процента массивных кровотечений при достижении целевого МНО 2,0-2,5 по сравнению с МНО 2,0-3,0 [4].…”
unclassified
“…Our meta-analysis of 10 studies involving 1349 patients receiving triple therapy revealed a weighted mean incidence of major bleeding at 30 days of 2.2% (95% confidence interval 0.7% to 3.7%; Table). [11][12][13][14][15][16][17][18][19][20] Most patients in these studies were receiving warfarin for AF and dual-antiplatelet therapy for a coronary artery stent. Although the studies contributing to these estimates were small, involved heterogeneous patient populations, employed different cointerventions, and used various definitions of major bleeding, they provide the best available estimates of bleeding risk associated with triple therapy.…”
Section: Safety Of Triple Therapymentioning
confidence: 99%